Hydromagnetic Blood Flow of Sisko Fluid in a Non-uniform Channel Induced by Peristaltic Wave. (July 2017) - Zeeshan, A.; Bhatti, M. M.; Akbar, N. S.; Sajjad, Y.
Abstract: In this paper, a smooth repetitive oscillating wave traveling down the elastic walls of a non-uniform two-dimensional channels is considered. It is assumed that the fluid is electrically conducting and a uniform magnetic field is perpendicular to flow. The Sisko fluid is grease thick non-Newtonian fluid can be considered equivalent to blood. Taking long wavelength and low Reynolds number, the equations are reduced. The analytical solution of the emerging non-linear differential equation is obtained by employing Homotopy Perturbation Method (HPM). The outcomes for dimensionless flow rate and dimensionless pressure rise have been computed numerically with respect to sundry concerning parameters amplitude ratio ϕ, Hartmann number M, and Sisko fluid parameter b 1 . The behaviors for pressure rise and average friction have been discussed in details and displayed graphically. Numerical and graphical comparison of Newtonian and non-Newtonian has also been evaluated for velocity and pressure rise. It is observed that the magnitude of pressure rise is maximum in the middle of the channel whereas for higher values of fluid parameter it increases. Further, it is also found that the velocity profile shows converse behavior along the walls of the channel against multiple values of fluid parameter.